High-sensitive cardiac troponin hs-TnT levels in sudden deaths related to atherosclerotic coronary artery disease. (August 2018) - Beausire, Tim; Faouzi, Mohamed; Palmiere, Cristian; Fracasso, Tony; Michaud, Katarzyna
Highlights: There is a significant association between hs-TnT serum values and the presence of ischemic heart disease as the cause of death. Cardiopulmonary resuscitation does not increase the hs-TnT levels. hs-TnT level increases in post-mortem, both in cases and controls. More studies on cardiac biomarkers are needed in postmortem practice. Abstract: Introduction: Ischemic heart disease (IHD) related to atherosclerotic coronary artery disease (CAD) is one of the most prevalent causes of death in Europe. Postmortem evaluation of IHD remains a challenge because of possible non-specific autopsy finding in some autopsy cases, especially in early myocardial ischemia. High-sensitive cardiac troponin T (hs-TnT) is used today in clinical practice as the "gold standard" to diagnose the myocardial ischemia, and might also be applied as an ancillary tool for post-mortem evaluation. Purpose: The goal of this study is to evaluate the diagnostic value of post-mortem serum hs-TnT assay in cases of sudden death related to IHD. We will also investigate the influence of cardiopulmonary resuscitation (CPR) attempts on post-mortem hs-TnT levels. Methods: The hs-TnT values in serum were retrospectively analysed in 85 autopsy data. 52 cases with clinical history and morphological results suggesting cardiac ischemia were included in the study group (mean age 53.5; age range 34–75) and 33 cases in the control group (mean age 40.4; age range 15–69). The group's statistical comparison was performed using logistic regression model. Results: Our study showed a significant non-linear association between hs-TnT serum values and post-mortem diagnosis of sudden deaths related to IHD ( p -value 0.005). The shape of the relationship is showing that the probability of death due to IHD increases quickly with a light level of hs-TnT (maximum around 90 ng/L) then decreases slightly while remaining at high in values. No significant difference in the hs-TnT serum values was found between the CPR and the non-CPR cases ( p -value 0.304). Conclusion: The measurement of hs-TnT serum values might be considered as an ancillary tool for the evaluation of death related to IHD, while taking necessary precautions in the interpretation of the results.